Pengaruh Ibadah Pagi terhadap Efektivitas Belajar Siswa SMA YP HKBP 1 - Eduward Situmorang; Monica Angelika Silitonga; Cindi Yarti Simanjuntak; Merlin Margaretha Boangmanalu; Rina Pefrianti Putri Sinaga; Anakki Augusterodin Simanjuntak (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the impact of morning worship on students’ learning effectiveness at SMA YP HKBP 1 by examining the synergy between spiritual and intellectual development. The research employed a case study design with a mixed methods approach. Quantitative data were collected through a learning spirituality questionnaire and academic test scores from 100 students selected using purposive sampling. Qualitative data were obtained through in-depth interviews, observations of morning worship activities, and school documentation. Quantitative data were analyzed using descriptive statistics and Pearson correlation tests, while qualitative data were examined using thematic analysis. The results indicate a significant improvement in students’ learning motivation, concentration, and average academic performance following the consistent implementation of morning worship. Qualitative findings reveal that morning worship contributes to the development of discipline, emotional stability, and students’ mental readiness for classroom learning. The study concludes that integrating spiritual practices through morning worship plays a positive role in enhancing learning effectiveness and supporting students’ character formation and academic achievement.